High-Resolution Spectroscopy of Winds Associated with T Tauri Stars. (February 2016) - Iguchi, Naoto; Itoh, Yoichi
Abstract: We carried out optical high-resolution spectroscopy of T Tauri stars using the Subaru Telescope. Using archived data from the Keck Telescope and the Very Large Telescope, we detected forbidden lines of [S II] at 4069 Å, in addition to those of [O I] at 5577 Å and 6300 Å, for 13 T Tauri stars. We consider that low-velocity components of these forbidden lines emanate from the wind associated with T Tauri stars. Using two flux ratios of the three lines, we simultaneously determined the hydrogen density and temperature of the winds. The winds of T Tauri stars have a hydrogen density of 2.5 × 10 6 cm −3 − 2.5 × 10 9 cm −3 and a temperature of 10800 –18 000 K. The mass loss rates by the wind are estimated to lie in the range from 2.0 × 10 −10 M ⊙ yr −1 to 1.4 × 10 −9 M ⊙ yr −1 . The mass loss rates are found to increase with increasing mass accretion rates. The ratio of the mass loss rate to the mass accretion rate is 0.001–0.1 for classical T Tauri stars and 0.1–1 for transitional disk objects.